2009
DOI: 10.1128/aem.02671-08
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Bacterial ATP Level and Proton Motive Force Due to Adhesion to a Solid Surface

Abstract: Bacterial adhesion to natural and man-made surfaces can be beneficial or detrimental, depending on the system at hand. Of vital importance is how the process of adhesion affects the bacterial metabolic activity. If activity is enhanced, this may help the cells colonize the surface, whereas if activity is reduced, it may inhibit colonization. Here, we report a study demonstrating that adhesion of both Escherichia coli and Bacillus brevis onto a glass surface resulted in enhanced metabolic activity, assessed thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 52 publications
5
61
0
1
Order By: Relevance
“…S8). This result is consistent with previous studies that show that starved E. coli cells maintain a significant pool of ATP, about 20%-60% of the total adenylate pool in adhered cells (22). Because murein remodeling is thought to be inhibited in nongrowing cells, these experiments indicate that cell-wall remodeling is not required for the decrease in stiffness upon the addition of A22.…”
Section: Changes In Cell Shape and Cell Growth Do Not Cause The Decresupporting
confidence: 92%
“…S8). This result is consistent with previous studies that show that starved E. coli cells maintain a significant pool of ATP, about 20%-60% of the total adenylate pool in adhered cells (22). Because murein remodeling is thought to be inhibited in nongrowing cells, these experiments indicate that cell-wall remodeling is not required for the decrease in stiffness upon the addition of A22.…”
Section: Changes In Cell Shape and Cell Growth Do Not Cause The Decresupporting
confidence: 92%
“…It was previously shown that the ATP levels of both E. coli and B. brevis adhered onto the glass surface were 2-5 times higher than that of corresponding planktonic bacteria (Hong and Brown, 2009). Then, using a bioenergetic model, it was shown that a change in pH in the periplasmic space of only 0.2-0.5 units was required to achieve these changes in ATP levels (Hong and Brown, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…It was previously shown that the ATP levels of both E. coli and B. brevis adhered onto the glass surface were 2-5 times higher than that of corresponding planktonic bacteria (Hong and Brown, 2009). Then, using a bioenergetic model, it was shown that a change in pH in the periplasmic space of only 0.2-0.5 units was required to achieve these changes in ATP levels (Hong and Brown, 2009). A key question remaining from the earlier study was whether a change in cell surface pH occurs upon adhesion that can result in this required pH change in the periplasmic space (i.e., the pH change at the cell surface is greater than or equal to the change required at the cytoplasmic membrane).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations